Humans Anticipate the Goal of other People’s Point-Light Actions - Elsner, Claudia; Falck-Ytter, Terje; Gredebäck, Gustaf (Frontiers in Psychology, 2012)
This eye tracking study investigated the degree to which low-level kinematic information from manual point-light (PL) displays provides sufficient information to elicit anticipatory eye movements. We compared gaze performance of adults observing a biological point-light animation of a manual reaching action or a non-biological version of the same event. Participants anticipated the biological motion PL display but not a non-biological control condition. The present study is the first to demonstrate that low-level kinematic information can be used to anticipate the goal of other people's point-light actions.